2023
DOI: 10.1002/tpg2.20301
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association mapping for pre‐harvest sprouting in European winter wheat detects novel resistance QTL, pleiotropic effects, and structural variation in multiple genomes

Abstract: Pre‐harvest sprouting (PHS), germination of seeds before harvest, is a major problem in global wheat (Triticum aestivum L.) production, and leads to reduced bread‐making quality in affected grain. Breeding for PHS resistance can prevent losses under adverse conditions. Selecting resistant lines in years lacking pre‐harvest rain, requires challenging of plants in the field or in the laboratory or using genetic markers. Despite the availability of a wheat reference and pan‐genome, linking markers, genes, allelic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Similar effects were observed for FN2, but the average FN in each haplotype class changed across the seasons ( Figure S5 ), and the effects for these two markers diminished in the prediction model due to a lower number of field trials with PHS-conducive conditions in the season 2015/2016 ( Figure 4 ). This is in accordance with previous studies where Phs-A1 appeared as one of the major QTL explaining up to 50% of the phenotypic variation for PHS-related traits [ 44 , 45 ]. Our results from weighting Phs-A1 as a fixed effect in the prediction model clearly underline the importance of this locus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar effects were observed for FN2, but the average FN in each haplotype class changed across the seasons ( Figure S5 ), and the effects for these two markers diminished in the prediction model due to a lower number of field trials with PHS-conducive conditions in the season 2015/2016 ( Figure 4 ). This is in accordance with previous studies where Phs-A1 appeared as one of the major QTL explaining up to 50% of the phenotypic variation for PHS-related traits [ 44 , 45 ]. Our results from weighting Phs-A1 as a fixed effect in the prediction model clearly underline the importance of this locus.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our study aimed at increasing the predictive accuracies by improving heritability through a better trait assessment independent of the weather conditions. In a recent study [ 44 ], PHS was assessed with the falling numbers after artificial rain and delayed harvest (FN2). Therefore, we compared FN2 with our in-house-established falling number stability test (FNS).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existence of a wheat reference and pangenome, a comprehensive understanding of the mechanisms governing different sources of PHS resistance remains limited. In this special section, Dallinger et al (2023) conducted a GWAS analysis and identified compelling evidence for novel QTLs associated with PHS resistance on chromosomes 1A and 5B. Several peaks on chromosome 4A were found to co-localize with the prominent resistance locus Phs-A1, containing causal genes TaPM19 and TaMKK3.…”
Section: Pre-harvest Sprouting Resistancementioning
confidence: 99%
“…In this special section, Dallinger et al. (2023) conducted a GWAS analysis and identified compelling evidence for novel QTLs associated with PHS resistance on chromosomes 1A and 5B. Several peaks on chromosome 4A were found to co‐localize with the prominent resistance locus Phs‐A1 , containing causal genes TaPM19 and TaMKK3 .…”
Section: Pre‐harvest Sprouting Resistancementioning
confidence: 99%